Language Transcendence Analysis of Tok Pisin Translation in The Shark Caller Novel - Adellia Putri Zahra (Universitas Sebelas Maret, 2024)
Tok Pisin is a Pidgin language that arose in Papua New Guinea and has become the most spoken language in the country. In order to translate Tok Pisin words incorporated in a novel, the translator must be aware of the Papua New Guinea culture and linguistic aspects presented in the novel. Thus, this research is intended to investigate the procedure of translating Tok Pisin words and phrases from the English novel The Shark Caller into the Indonesian adaptation Sang Pemanggil Hiu. This research employed a qualitative method with an explanatory case study employing Peter Newmark’s theory or translation procedure. The investigation revealed ninety-four data, which consisted of eighty-seven words and seven phrases. The researcher identified nine procedures applied by the translator: couplets, synonyms, literal translation, modulation, transference, transposition, paraphrase, cultural equivalence, and reduction. Among these, couplets were the most frequently applied, with 25 data points. Additionally, this research revealed that the Tok Pisin words adhere to English grammar. Thus, numerous double meanings result from the use of Tok Pisin words in English sentences; therefore, the translator frequently omits them in the target text. Consequently, the translator sacrificed certain Papua New Guineans in favor of a comprehensible translation.